Differing Expression of Cytokines and Tumor Markers in Combined Pulmonary Fibrosis and Emphysema Compared to Emphysema and Pulmonary Fibrosis. (30th March 2017) - Xu, Ling; Bian, Wei; Gu, Xiao-hua; Shen, Ce
ABSTRACT: This study aimed to explore the different pathogeneses of combined pulmonary fibrosis and emphysema (CPFE) from emphysema and pulmonary fibrosis. The levels of transforming growth factor-β1 (TGF-β1 ), vascular endothelial growth factor (VEGF), Krebs Von Den Lungen-6 (KL-6), matrix metalloproteinase-9 (MMP-9), tissue inhibitors of metalloproteinases-1 (TIMP-1), cytokeratin 19 fragment (CYFRA21-1), squamous cell carcinoma antigen (SCC), and the telomerase activity in peripheral blood were measured in 38 CPFE patients, 50 pulmonary emphysema patients, and 34 idiopathic pulmonary fibrosis (IPF) patients. The results demonstrated that the levels of VEGF and TGF-β1 in IPF patients were significantly higher than those in emphysema patients ( p < 0.05), and no significant differences were detected between CPFE patients and other two groups ( p > 0.05). The levels of KL-6 and CYFRA21-1 in IPF patients were significantly higher than those in emphysema and CPFE patients ( p < 0.05), and the latter had the similar levels ( p > 0.05). Among the three groups, the levels of SCC, MMP-9, TIMP-1, MMP-9/TIMP-1 ratio, and telomerase activity were not different ( p > 0.05). Our study showed that VEGF, TGF-β1, KL-6, and CYFRA21-1 may play a role in the pathogenesis of pulmonary fibrosis. The lower levels of KL-6 and CYFRA21-1 in CPFE patients may be one of the reasons why these patients develop emphysema on the basis of fibrosis.